Effect of industrial actions-induced psychological stress on academic performance of students In Nigerian universities (2021)
The effect of repeated disruptions of teaching and learning on students’ academic performance can better be imagined than described. Tertiary institutions, the engine room for the workforce in Nigeria has thus suffered tremendous setbacks as a result of industrial actions. The study investigated the effect of stress caused by industrial actions on student academic performance of Nigerian Universities. This study was guided by three research questions and one hypothesis. The descriptive survey method was adopted for the study. The target population for this study consists of all undergraduates from universities in South-west Nigeria. The purposive sampling technique was used to sample six federal universities as the group is the most affected by the industrial actions. From each university, a proportionate to size sampling technique was used to select 1,220 off-campus students that participated in the study. Four instruments used for data collection are Psychological Effect of Strike Questionnaire (PESQ), 1-0.82, Spielberger’s State Anger Scale (SSAS), r=0,78, Hopkins Symptom Checklist Anxiety Scale (HSCAS), r=0.84 and General Study Achievement Test (GSAT), r=0.87. The result indicates that there is a composite relationship (β =0.75, p<0.05) between psychological stress and academic performance. It also reveals that all the psychological factors, anger (β=0.27, t=6.37), anxiety (β =0.16, t=3.50), self- efficacy (β =0.11, t=3.90), student plan (β =0.04, t=l.21) contributed significantly to the prediction of student academic performance. It is therefore recommended that all stakeholders must understand the grievous effect of strike on student academic performance and should therefore imbibe the spirit of collective bargaining.